Financial Literasi pada Perilaku Konsumtif pada Generasi Z - Sahrullah, Sahrullah; Machmud, Mulyana (Amsir Accounting & Finance Journal, 2023)
The purpose of this research is to determine the level of financial literacy and the level of consumer behavior and to investigate whether there is a significant influence between these variables. The method used is a quantitative method. Data collection was carried out by distributing questionnaires to 400 students in Parepare City using probability random sampling. The data analysis techniques used were descriptive analysis and simple linear regression analysis. Students in Parepare City showed good financial literacy levels in basic aspects, but lacked knowledge in advanced financial areas. Their consumer behavior can be considered good, although there are some areas that require special attention. The regression analysis results indicate that the higher the financial literacy level, the lower the consumer behavior, supported by the t-test showing a significant influence. However, the contribution of financial literacy to consumer behavior is only about 15.9%, with other unexamined factors also playing a role. Therefore, efforts are needed to improve students' financial literacy, especially in understanding advanced financial aspects, to more effectively reduce unnecessary consumer behavior. The hypothesis test results conclude that H₀ (null hypothesis) is rejected.